Au/Cdot-Nanohybrid Electrocatalyst Synthesized by Rice-Straw-Derived Carbon Dots as a Reducing Agent for Improved Hydrogen Evolution Reactions. Issue 4 (12th April 2021) - Nguyen, Ngoc-Anh; Le, Thi-Hien; Trinh, Van-Huy; Ngo, Quang-Tung; Nguyen, Van-Toan; Lee, Gilhwan; Choi, Ho-Suk; Chen, Guangliang
Abstract : We report a facile method by which to synthesize Au/Cdot nanohybrids using carbon dots (Cdots) obtained from rice straw as a direct reducing agent as well as a stabilizer. Rice-straw-derived Cdots possess oxygen-containing functional groups that act as an electron-donating source to reduce Au 3+ to Au 0 without the use of chemical reagents for the reduction of Au precursors. Additionally, the strong Au-carbon interaction promotes a high electron transfer of the Au/Cdot nanohybrid electrocatalyst, resulting in enhanced performance of the hydrogen evolution reaction (HER). The overpotential is 150 mV at a current density of 10 mA·cm −2 and the TOF value is 0.06·s −1, representing the most outstanding HER performance among Au-based catalysts as a non-Pt HER electrocatalyst. The HER activity is stably maintained for 2000 cycles as well as for 48 h. The synthesis of Cdots, the hybridization of Au/Cdot electrocatalyst, and the production of clean hydrogen fuel using Au/Cdots are zero CO2 emission strategies, not only preventing the emission of pollutants but also satisfying the energy needs of humankind.